Pengaruh Budaya Kerja dan Kepuasan Kerja terhadap Kinerja Pegawai PT Kereta Api Indonesia Divre III Palembang - Syafitri Adilah; Hamid Halin; Muhammad Kurniawan (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this research is to examine how PT Kereta Api Indonesia Divre III Palembang's work culture and workers' levels of job satisfaction affect productivity. The research is quantitative, including techniques like multiple linear regression. A total of 133 participants were included in the analysis, which was conducted in SPSS version 24. Probability sampling's simplest form, known as "simple random sampling," was used to choose the samples. Work culture (X1) and job satisfaction (X2) were shown to have no influence and were not partly significant on employee performance, as determined by the t test. The f test results in this study also show that neither the work culture variable (X1) nor the job satisfaction variable (X2) had any influence on employee performance. This provides evidence against the hypothesis being tested. The subsequent R2 value of 0.024, or 2.4%, explains that neither the work culture variable (X1) nor the job satisfaction variable (X2) have a substantial impact on employee performance.